2017
DOI: 10.1007/s00284-017-1348-1
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Expression in Aspergillus niger of an Antibody Fused to Leishmania sp. Antigens

Abstract: Nucleoside hydrolase and sterol 24-c-methyltransferase, two antigenic proteins of Leishmania sp., were expressed in Aspergillus niger. Genetic transformation of conidia was achieved using underwater shock waves. scFv antibody addressed to DEC205, a receptor of dendritic cells, was fused to two proteins of Leishmania sp. Receptor 205 has a relevant role in the immune system in mammals; it can modulate T cell response to different antigens. Extracellular expression strategy of recombinant antibody was achieved u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Filamentous fungi serve as a cell platform mainly for the production of large-scale industrial enzymes. However, due to certain features, such as very fast and strong growth and the ability to release large amounts of proteins directly to the substrate, this platform is used more widely for the production of recombinant proteins [17, 18]. It was reported that fungi such as Aspergillus niger were able to produce and secrete c.a.…”
Section: Comparison Among the Production Systems Of Recombinant Prmentioning
confidence: 99%
“…Filamentous fungi serve as a cell platform mainly for the production of large-scale industrial enzymes. However, due to certain features, such as very fast and strong growth and the ability to release large amounts of proteins directly to the substrate, this platform is used more widely for the production of recombinant proteins [17, 18]. It was reported that fungi such as Aspergillus niger were able to produce and secrete c.a.…”
Section: Comparison Among the Production Systems Of Recombinant Prmentioning
confidence: 99%
“…Recently, two fusion proteins each consisting of a highly antigenic protein from Leishmania sp. , an antibody specific for a receptor of dendritic cells, and a fragment of native glucoamylase A were generated in A. niger (Magana-Ortiz et al 2018). Both recombinant proteins may be used for immunization against Leishmaniasis and point to the potential of filamentous fungi as hosts for the generation of pharmaceutically relevant peptides.…”
Section: Production Of Heterologous Productsmentioning
confidence: 99%
“…In addition, due to their saprophytic lifestyle, most filamentous fungi have already developed the ability to produce and secrete a vast amount of enzymes in order to break down and feed on organic matter [11]. Strains belonging to the genera Aspergillus, Trichoderma, and Neurospora are in fact widely used for production of recombinant proteins with industrial applications [12][13][14][15]. Several reviews have described the potentials of filamentous fungi in the production of pharmaceutical and other industrial proteins, as well as the genetic engineering approaches followed to maximize production levels [7,16,17].…”
Section: Introductionmentioning
confidence: 99%